Changes in Refractory Black Carbon (rBC) Deposition to Coastal Eastern Antarctica During the Past Century. Issue 8 (15th August 2022) - Li, Chuanjin; Ma, Xiangyu; Dowdy, Andrew; Wang, Xiaoming; Ding, Minghu; Du, Zhiheng; Wang, Xiaoxiang; Cui, Xiaoqing; Gao, Shaopeng; Liu, Yan; Kang, Shichang; Xiao, Cunde
Abstract: Refractory black carbon (rBC) is an important climate‐forcing agent emitted by biomass burning and fossil fuel combustion. Antarctica can receive rBC aerosols emitted in Southern Hemisphere (SH) and preserve the history of emissions and atmospheric transport. Here, we present a high‐resolution record of rBC in an ice core (CA2016‐75) acquired from the coastal Eastern Antarctica, which accumulated during the past 100 years (1915–2015). The rBC concentration (0.030 ng g −1 ) and flux (7.22 μg m −2 yr −1 ) are both among the lowest values in Antarctic snow and ice. The rBC concentration reaches higher values on average in the period aligned with the austral Winter. The rBC concentrations show a long‐term descending trend during the period between 1950s and mid‐1990s, followed by an ascending trend to 2015. Back trajectory analysis indicates that the emissions resulting from the biomass burning and anthropogenic biofuel consumption in Southern America and Australia were the main sources for the rBC deposition. Wavelet spectral analysis and temporal correlation analysis on rBC deposition and the atmospheric circulation indices (El Niño–Southern Oscillation, Southern Annular Mode and Antarctic Oscillation) confirmed that the atmospheric circulations have certain influences on the rBC deposition, likely by their direct effects on rBC transport and on weather conditions driving the occurrence of fires and subsequent emissions in source regions. Key Points: Yearly resolution black carbon (BC) data during the past century in east Antarctica were presented and showed the lowest BC values over Antarctica BC showed a decrease between 1980s and mid‐1990s and then an increase to 2015, the variation was associated with the BC emissions in Southern Hemisphere Southern America, Australia were the potential source regions and the El Niño–Southern Oscillation, Southern Annular Mode both had influences on BC transport and source emissions